AKTOR, AKSES DAN POLITIK LINGKUNGAN DI PERTAMBANGAN TIMAH BANGKA - Erman, Erwiza (Masyarakat Indonesia, 2010)
Tin has been exploited since the early 18th century in the island of Bangka. Since that time, this extractive industry has been a leading export commodity and has given important contributions to the state revenue. Despite already being mined for more than three centuries, only since the Reform era (1998), there has been a series of long and controversial debates over the control of tin resources and its environmental impact. The debates have on this issue has been conducted intensively from 2000 until 2007. However, when the second governor of the province was nominated in 2007, criticisms were reduced, particularly when Babel Hijau Lestari was created by the Governor in July 2007. This article tries to elucidate the issues on the control over tin resources and environmental damages as a window of opportunity to observe the political motivations of state actors and the local community behind the debates. Unlike the general perception, state actors and the local community are not homogeneous entities. Their views over control of mines and environmental issues are fragmented and contradictory with each other. The different point of views of actors cannot be separated from their struggles to gain political and economic accesses. By looking at a trajectory of control over tin resources, its impact on environment, and the responses of the actors to it, soon we will discover a different environmental politics in relation to the struggles of actors in the period of decentralization and local autonomy.